2023
DOI: 10.1111/evj.14009
|View full text |Cite
|
Sign up to set email alerts
|

BEVA primary care clinical guidelines: Diagnosis and management of equine pituitary pars intermedia dysfunction

Nicola J. Menzies‐Gow,
Heidi E. Banse,
Aimi Duff
et al.

Abstract: BackgroundPituitary pars intermedia dysfunction (PPID) is a prevalent, age‐related chronic disorder in equids. Diagnosis of PPID can be challenging because of its broad spectrum of clinical presentations and disparate published diagnostic criteria, and there are limited available treatment options.ObjectivesTo develop evidence‐based primary care guidelines for the diagnosis and treatment of equine PPID based on the available literature.Study designEvidence‐based clinical guideline using the Grading of Recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…1,2 This relatively high prevalence, especially in aged animals, reinforces the importance of the selection of PPID as the topic for development of British Equine Veterinary Association (BEVA) primary care clinical guidelines, which are included in this special collection. 3 The goal of these guidelines is to provide evidence-based recommendations for the diagnosis and management of PPID directed at equine practitioners in an ambulatory setting. The panel utilised a previously established framework to identify clinical questions relevant to PPID, and to make recommendations related to those questions based on appraisal of the currently available literature.…”
Section: Update On Ppidmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 This relatively high prevalence, especially in aged animals, reinforces the importance of the selection of PPID as the topic for development of British Equine Veterinary Association (BEVA) primary care clinical guidelines, which are included in this special collection. 3 The goal of these guidelines is to provide evidence-based recommendations for the diagnosis and management of PPID directed at equine practitioners in an ambulatory setting. The panel utilised a previously established framework to identify clinical questions relevant to PPID, and to make recommendations related to those questions based on appraisal of the currently available literature.…”
Section: Update On Ppidmentioning
confidence: 99%
“…The panel utilised a previously established framework to identify clinical questions relevant to PPID, and to make recommendations related to those questions based on appraisal of the currently available literature. [3][4][5] Hypertrichosis and altered/delayed hair coat shedding have long been described as an extremely common, almost pathognomonic, clinical sign of PPID in equids. 6,7 That assessment is supported by the evidence review conducted by Menzies-Gow and colleagues, which found evidence for a high clinical suspicion of PPID in animals with haircoat changes and stressed the importance of considering both animal age and clinical signs in case selection for PPID testing.…”
Section: Update On Ppidmentioning
confidence: 99%
See 2 more Smart Citations
“…EVJ is proud to have published BEVA Primary Care Clinical Guidelines on analgesia, 6 wound management 7 and pituitary pars intermedia dysfunction 8 . We are equally delighted to have published a small but growing group of systematic reviews, particularly in recent years, where high‐quality evidence is now available for equine anaesthesia, 9–11 PPID 12 and laminitis, 13,14 spinal disorders, 15 respiratory disorders, 16,17 lameness in working equids, 18 clinical predictive models, 19 vaccine efficacy, 20,21 sarcoid treatment, 12 use of furosemide, 22 reproduction, 23,24 physiotherapy, 25 diagnostic imaging 26 and on the prevalence of a range of infectious diseases 27–32 .…”
mentioning
confidence: 99%